Response of splenic melanomacrophage centers of Oreochromis niloticus (Linnaeus, 1758) to inflammatory stimuli by BCG and foreign bodies - Manrique, W. G. [UNESP]; Silva Claudiano, G. da [UNESP]; Petrillo, T. R. [UNESP]; Pardi de Castro, M. [UNESP]; Pereira Figueiredo, M. A. [UNESP]; Andrade Belo, M. A. de [UNESP]; Engracia de Moraes, J. R. [UNESP]; Ruas de Moraes, F. [UNESP] (Wiley-Blackwell, 2014)
The study objective was to make histological, histochemical and morphometric evaluations on the splenic Melanomacrophage centers (MMCs) of tilapias, Oreochromis niloticus (Linnaeus, 1758), that were subjected to chronic inflammation stimuli by implantation (IMP) of a glass coverslip in the subcutaneous tissue and through inoculation of the bacillus Calmette-Guerin (BCG). Randomly distributed in four groups were 150 tilapias: IMP (n = 45); IMP+ BCG (n = 45); BCG (n = 45); and control (n = 15). Nine fish per treatment and three control fish were sampled on days 3, 7, 14, 21 and 33. The results demonstrated that increased numbers and areas of these structures were related to the type of stimulus, and that these were greater for the specific response. The principal pigment component identified was hemosiderin. Results suggest that the intensity of the MMC response in O. niloticus depended on the type of inflammatory stimulus used, and that it was greater in fish inoculated with BCG, which induced a granulomatous inflammation when compared to the foreign body inflammatory response induced by the glass coverslips.